The Influence of The Students' Perceptions About Teacher Professional Education Program (PPG) on The Interests in Becoming Certified Teachers - Putri, Riska Defia; Latiana, Lita (BELIA: Early Childhood Education Papers, 2020)
The purpose of this study was to determine the influence of the students’ perceptions about Teacher Professional Educational Program (PPG) on the interest in becoming a certified teacher in the Early Childhood Teacher Education (PGPAUD) study program, faculty of education, UNNES. Students’ perceptions about PPG and interest in becoming certified teachers are interrelated. One of the requirements for someone wanting to become a professional teacher and having certification has to take PPG. The program is aimed at graduates of S1 / D4 education and non-education. The approach used is quantitative with survey methods. The populations of this study are the active students of PGPAUD UNNES 2017. The number of samples that have been taken using a proportional random sampling technique is 78 students from 3 classes. The data collection techniques used a questionnaire. All calculations use SPSS 24. Based on statistical calculations using Linear Regression, a significance value (Sig.) Of 0.00 is obtained, which means it is smaller than the significance level of 0.05 or 0.00 <0.05, then Ha is accepted. The results of the study using simple linear regression analysis showed there was an effect of 59.4% and the remaining 40.6% was influenced by other factors not covered in the study. This shows that students' perceptions about PPG have an influence on the interest in becoming a certified teacher. This research suggests that educational student graduates must be more enthusiastic and increase their confidence to be able to compete with non-education students to become certified, competent, and professional teachers.